2004
DOI: 10.3748/wjg.v10.i12.1810
|View full text |Cite
|
Sign up to set email alerts
|

Association of -238G/A polymorphism of tumor necrosis factor-alpha gene promoter region with outcomes of hepatitis B virus infection in Chinese Han population

Abstract: AIM:To clarify whether -238G/A polymorphism of tumor necrosis factor-α (TNF-α) gene promoter region was associated with outcomes of hepatitis B virus (HBV) infection in Han population of northern China, and to analyze the geneenvironment interaction between -238G/A polymorphism and cigarette smoking or alcohol consumption. METHODS:A case-control study was conducted to analyze the association of TNF-α gene promoter polymorphism with HBV infection outcomes. A total of 207 patients with chronic hepatitis B (HB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
2
17
2
1
Order By: Relevance
“…However, the results differed from the study of Lu et al [32]. The current results suggest that ethnicity may have played an important role in HBV infection outcome, leading to results inconsistent with that of others.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results differed from the study of Lu et al [32]. The current results suggest that ethnicity may have played an important role in HBV infection outcome, leading to results inconsistent with that of others.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the expression of TNF-α is affected by SNPs, but we did not find any difference among -238 A/G genotypes with regard to the serum levels of TNF-α. In accordance with our findings, Du et al (34) and Lu et al (35) reported an association between the -238 GG genotype and HBV infection. The current study indicated a relative increase in the frequency of -238 GG genotype and G allele in HBV infected patients; but it was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…Other genes that could influence the course of viral infections, for example cytokine‐encoding genes, also show some limited polymorphism. It was demonstrated that a single nucleotide polymporphism (SNP) in the TNF‐α gene promoter at position – 238 leading to low TNF‐α production was associated with a more severe clinical course of PUUV infection (290) and the development of chronic active hepatitis B and C (291, 292). TNF‐α is especially important for elimination of non‐cytopathic viruses like hepatitis B and C virus, as it can purge viruses from infected cells without lysing them and, therefore, without collateral damage (237).…”
Section: Immune Response To Hantaviruses In Humansmentioning
confidence: 99%